Epidermodysplasia verruciformis: a case report - Alam, Mansurul; Barua, Barnali; Mowla, Md Rafiqul; Ullah, GM Zakawat; Rahman, Md Habibur; Dey, Nishith Ranjan; Hoque, Roksana; Ahmad, Mostafa Khaled (Journal of Chittagong Medical College Teachers' Association, 2011)
Keywords: papilloma virus; cauliflower like growth; skin grafting DOI: http://dx.doi.org/10.3329/jcmcta.v22i1.9113 JCMCTA 2011; 22(1): 43-46